Breast-stroke motor pattern - Nemessuri, M.; Vaday, M. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
The breast-stroke is in many lands the most popular way of swimming. Namely the breast-stroke gives the ordinary swimmer greater security in water. Fatigue sets in later than with crawl-stroke or the dolphin. Visibility is better than with back stroke and breathing is relatively simpler than with other types of swimming. The purpose of our analysis was to measure the main factors of the motor process of swimming. In this way it is possible to get better aquainted with the characteristic form of human locomotion and to draw conclusions on an improvement in the efficiency of swimming.